Application of positive psychology to human formation of priests and religious: the active program of positive personal development (APPRO) - Piotr Kwiatek (The Francis de Sales Scientific Society (TNFS.PL), 2022)
This article presents a specific opportunity to apply the knowledge of positive psychology in furthering the human formation of clergy and religious.  The APPRO program was conceived specifically to address the needs of seminarians, priests, and consecrated persons in their initial formation as well as their continuing personal growth for effective ministry.   It focuses on the psy-chological well-being of the individual which undoubtedly can enhance and optimize the ongoing formation of the person.